Pengaruh Kualitas Produk, Lokasi Usaha, dan Inovasi Produk terhadap Keunggulan Bersaing pada Teh Kota di Parakan, Kabupaten Temanggung, Jawa Tengah - Yustika Choirun Nisa; Edi Murdiyanto; Nuril Aulia Munawaroh (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of product quality, business location, and product innovation on competitive advantage at Teh Kota in Parakan, Temanggung Regency. The research employs a quantitative method, with samples selected using purposive sampling techniques involving 96 respondents who are consumers of Teh Kota. Data were collected through questionnaires and analyzed using various statistical techniques, including validity tests, reliability tests, classical assumption tests, Rank Spearman correlation analysis, multiple linear regression, t-tests, and F-tests. The results indicate that, partially, business location has a significant effect on competitive advantage, with a significance value of 0.0011 (< 0.05). In contrast, product quality and product innovation do not show a significant partial effect on competitive advantage, with significance values of 0.436 and 0.964 (> 0.05), respectively. However, when analyzed simultaneously, product quality, business location, and product innovation have a significant effect on competitive advantage, as indicated by a significance value of 0.043 (< 0.05). These findings suggest that while location plays a dominant individual role, the combined implementation of quality, location, and innovation strategies remains essential for enhancing business competitiveness.